A new software-based methodology for applying Laubscher’s empirical charts to estimate caving angles and evaluate subsidence surfaces in caving mining projects - Montoya, J; Morales, J; Hamman, E (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Laubscher’s empirical charts for the estimation of cave angles are widely used in caving mining as a straightforward method for estimating the extension of the zone affected by caving. This method is usually applied in two vertical sections (e.g. north–south and east–west) and considers a simplified geometry of the planned mine. In this article a new methodology for the application of Laubscher’s empirical method is proposed, based on a 3D block model with detailed information of rock mass (RMR90) and mine geometry. The use of the block model makes it possible to identify the zones potentially affected by the mining process, and to define in detail the adjustments required for the calculation of mining rock mass rating (MRMR) due to water, weathering, joints orientation, mining-induced stresses and blasting. The representation of the mine inside the block model allows one to explicitly consider the effects of geometry changes between sublevels in the shape and extension of the final caving surface. Laubscher’s methodology was automatised using R programming language, making it possible to perform the analysis in multiple vertical sections (e.g. 180 sections every 1° azimuth) and to evaluate the sensitivity of the results to the input parameters in a fast and efficient way. The main results of the proposed methodology are the 3D empirical caving surface and the subsidence area associated with the planned mine. The methodology was applied during the feasibility study of a sublevel caving mining project in Colombia, with very good agreements between the empirical estimation of the caving surface and the results of subsequent numerical modelling. The proposed methodology could become a powerful tool in the planning of caving mining projects, including the design of critical infrastructure and the evaluation of environmental impacts.
Keywords: cave angles; subsidence; block model; RMR90; MRMR; mine geometry; Laubscher’s empirical charts